Sports-related sudden cardiac death attributable to myocarditis: a systematic review and meta-analysis - Quinn, R.; Moulson, N.; Wang, J.; Isserow, S.; McKinney, J. (Canadian Journal of Cardiology, 2022)
Background: The incidence of sports-related sudden cardiac death (SrSCD) attributable to myocarditis is unknown. With the known association between SARS-CoV-2 (COVID-19) and myocarditis, an understanding of pre-pandemic rates of SrSCD due to myocarditis will be important in assessing a change of risk in the future. The objective was to ascertain the incidence of SrSCD or aborted sudden cardiac death (SCD) attributable to myocarditis in the general population. Methods: A literature search through PubMed/Medline and Ovid/Embase was completed. Studies of SrSCD with autopsy data or clear-cause-aborted SrSCD were included. SrSCD was defined as SCD which occurred within 1 hour of exercise. Data were abstracted by 2 independent reviewers using the MOOSE guidelines. Risk assessment was performed with the Joanna Briggs Institute Critical Appraisal Checklist for Prevalence Studies. Random effects models were used to report the incidence and 95% CIs. The primary outcome was the incidence of SrSCD attributable to myocarditis, and the secondary outcome was SrSCD overall. Results: Fifteen studies were included comprising 347,092,437 person-years (PY). There were 1955 SrSCD or aborted SrSCD overall with an incidence of 0.93 (95% CI 0.47-1.82) per 100,000 PY. Fifty-three SrSCD were attributed to myocarditis with an incidence of 0.047 (95% CI 0.018-0.123) per 100,000 PY, or 1 death attributable to myocarditis in 2.13 million PY. Conclusions: In this meta-analysis, the overall incidence of SrSCD was low. Furthermore, SrSCD attributed to myocarditis is exceedingly rare.